Content knowledge in mathematics with arts integrated learning: A study on high emotional intelligence - Hartatik, Sri; Juniati, Dwi; Sulaiman, Raden (Edelweiss Applied Science and Technology, 2025)
This study aims to describe the content knowledge of Elementary School Teacher Education students with High Emotional Intelligence (EI) in Mathematics learning the area of flat shapes integrated with art. This study used a descriptive explorative approach with qualitative methods. Data were collected through in-depth interviews, observations, and document analysis related to lesson plans and task completion. College students with high EI demonstrate strong content knowledge of flat shape areas integrated with art, as shown by five indicators: they can explain the area concept correctly, present clear and relevant methods with examples, simplify formula derivation, relate area concepts to art (music, dance, drama, visual art), and clearly explain problem-solving procedures in an art context. High EI content knowledge in art-integrated plane figure area learning is linked to Emotional Intelligence aspects, including management skills, empathy, problem-solving, emotional regulation, self-motivation, and self-awareness. The conclusion of this study shows that elementary school teacher education college students with high EI in Mathematics learning the area of flat shapes integrated with art have strong content knowledge.